Post-Truth Society dan Pendidikan Islam: Membentuk Karakter Kritis-Religius Generasi Alpha - Anita Puspa Meilina; Roziman Roziman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The post-truth phenomenon has posed significant challenges to education, particularly Islamic education, in shaping a young generation that is both critical and religious. Generation Alpha, born and raised in a digital ecosystem, faces an overwhelming flow of information, disinformation, and opinion manipulation that often blurs the line between fact and falsehood. This study aims to analyze how Islamic education can respond to the post-truth crisis by fostering a critical-religious character among Generation Alpha. This research employs a qualitative library-based method, utilizing content analysis that integrates classical Islamic sources on epistemology such as al-haqq and tabayyun with contemporary findings on digital literacy and the psychosocial development of Generation Alpha. The findings indicate that Islamic education should focus on strengthening Islamic digital literacy, promoting dialogical learning that cultivates critical thinking, and integrating strong spiritual values. Curriculum transformation, the role of teachers as epistemic role models, and the support of families and communities are essential in creating an educational ecosystem capable of countering post-truth influences. Thus, Islamic education serves as both a moral and intellectual safeguard, protecting Generation Alpha from the crisis of truth while preparing them to be critical, adaptive, and religious Muslims in the digital age.